Spinal injuries in sports - Boden, B. P.; Jarvis, C. G. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Athletic competition has long been a known source of spinal injuries. Approximately 8.7% of all new cases of spinal cord injuries in the United States are related to sports activities. The sports activities that have the highest risk of catastrophic spinal injuries are football, ice hockey, wrestling, diving, skiing, snowboarding, rugby, and cheerleading. Axial compression forces to the top of the head can lead to cervical fracture and quadriplegia in any sport. It is critical for any medical personnel responsible for athletes in team sports to have a plan for stabilization and transfer of an athlete who sustains a cervical spine injury.